Geeky f@b 5. #3, DOGgone CATastrophe - Lareau, Lucy; Lareau, Liz (Papercutz, 2019)
"When a tornado rips through the town of Normal, the local animal shelter is devastated leaving many animals needing emergency homes and care. The Geeky F@b 5 are up to the challenge and rally all of Earhart Elementary School to help. Sofia gets busy helping code a matchmaking program to match the pets to households and A.J. fits a harness for a handicapped basset hound. But can Marina get over her fear of snakes to help some in need? Join these 5 girls, and that sassy cat Hubble, as they learn that friendship isn't always just a human thing!"--Back cover.